Pemanfaatan Flipbook Interaktif sebagai Inovasi Pembelajaran Digital dalam Meningkatkan Motivasi dan Partisipasi Belajar Siswa - Muhammad Kholil; Muhammad Su'aidi Ali; Mohammad Hamdan (Transformative Service Journal, 2025)
This community service activity aimed to utilize interactive flipbooks as a digital learning innovation to enhance students’ learning motivation and participation. The activity was conducted at MI Syafi’iyah NU Tarokan Banyuanyar Probolinggo, involving teachers and students through a Participatory Action Research (PAR) approach, which included the stages of planning, implementation, observation, and reflection. Data were collected using pre-test and post-test instruments to measure changes in students’ motivation and participation before and after the implementation of interactive flipbooks. The results showed a significant improvement in students’ learning motivation and participation, as indicated by an increase in motivation scores from 62% to 90% and participation scores from 55% to 90%. These findings demonstrate that interactive flipbooks contribute positively to creating a more engaging, participatory, and student-centered learning environment. Therefore, interactive flipbooks can be recommended as an effective and sustainable digital learning innovation to improve the quality of classroom learning